Integrating Ecotheology and Participatory Learning to Foster Students’ Ecological Awareness - Teguh Aryanto; Na’imah Na’imah; Sigit Prasetyo; Shaleh Shaleh (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
This study examines the internalization of Islamic ecotheological values through participatory learning at Madrasah Tsanawiyah Sunan Pandanaran Yogyakarta. Using a qualitative descriptive approach, this study explores how theological principles are transformed into ecological awareness and behavior. The results show that Islamic ecotheology functions as an ontological foundation that reconstructs students' paradigms from an anthropocentric theological perspective to an ecocentric one. Pedagogical strategies that include contextual reinterpretation, integration of cosmic empathy, and prophetic examples (uswah) serve as tools for deep internalization, changing students' motivation from extrinsic obedience to autonomous spiritual trust (amanah). Furthermore, this study identifies participatory learning as a crucial pedagogical mediation to bridge the gap between values and actions. By involving students in reflective dialogue and collective ecological projects, schools successfully fostered a stable and autonomous ecological habitus. This discussion synthesizes these findings with transformative learning theory, highlighting that the eschatological spiritual dimension provides a more sustainable basis for environmental preservation than a purely technical approach. This study contributes a conceptual model for integrating spiritual values into practical ecological action, offering a transformative framework for Islamic religious education in response to the contemporary environmental crisis.